Assessing Unmet and Latent Demand for Pharmacists at the State Level - Prachi Arora; David A. Mott; Michelle A. Chui; David H. Kreling (University of Minnesota Libraries Publishing, 2015)
Background: Past reports suggest that a near balance has been reached in the supply and demand for pharmacists in the US. Although data on the level of supply of pharmacists is available, there is no continuous and systematic tracking of the level of demand (unmet and latent) for pharmacists at state level. Unmet demand, an established construct in pharmacy workforce, is important to measure the number of vacancies and assess pharmacist shortage consistently over time. Latent demand or potential demand is a novel construct and has never been measured in pharmacy workforce. With the increase in supply, it is important to measure the potential demand that could be budgeted in pharmacies in the near future. Objective: The objective of this study was to measure the unmet and latent demand for pharmacists and explore the association between latent demand and workload characteristics in community and hospital pharmacies in Wisconsin in 2011-12. Methods: The study used a cross-sectional, descriptive survey design. A sample of community pharmacies (n=1,064) and hospital pharmacies (n=126) licensed in Wisconsin in 2011-12 was identified. Key informants (managers/owners) of sampled pharmacies were sent a one-page cover letter explaining the purpose of the study and requesting participation and a three page survey form. The main outcome measures of the study were total number of FTE pharmacist positions vacant, presence of adequate staff size, additional number of FTE pharmacist positions needed to attain adequate staff size, prescription volume, daily census, hospital size and number of hours prescription department is open. Descriptive statistics were calculated for all the pharmacies collectively, then separately for community and hospital pharmacies. Pharmacy setting, vacancies and workload characteristics of pharmacies with and without latent demand were compared using chi-squared test of independence and/or t-test. Sample weights were calculated and used in all the analyses to weigh the estimates to all pharmacies in Wisconsin. Results: Overall response rate to the survey was 50.1%. Of the total number of FTE pharmacist positions budgeted in Wisconsin, 54.3 FTE positions (1.5%) were reported vacant in 2011-12. Approximately 28.2% of the community and hospital pharmacies reported the presence of latent demand. Latent demand was significantly associated with higher workload in community pharmacies and larger bed size in hospital pharmacies. Conclusion: There appeared to be a balance between the supply and demand for pharmacists in Wisconsin in 2011-12. There is a potential for additional FTE positions (latent demand) to be budgeted in pharmacies to attain adequate pharmacist staff size. It is important to consistently track the level of unmet and latent demand for pharmacists in Wisconsin and combine this information with other workforce characteristics to guide the decision making of pharmacy workforce planners and pharmacy managers.   Type: Original Research